2023
DOI: 10.1111/jne.13236
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin antagonist does not disrupt rabbit maternal behavior despite binding to brain oxytocin receptors

Abstract: We explored a possible role of oxytocin (OXT) for the onset and maintenance of rabbit maternal behavior by: (a) confirming that a selective oxytocin receptor antagonist (OTA) widely used in rodents selectively binds to OXT receptors (OXTR) in the rabbit brain and (b) determining the effect of daily intracerebroventricular (icv) injections of OTA to primiparous and multiparous does from gestation day 29 to lactation day 3. OTA efficiently displaced the high affinity, selective oxytocin receptor (OXTR) radioliga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 65 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…The investigations of OXT in different anatomical regions and compounds are another research field. Recent studies in rabbits have shown that OXT antagonist administration does not impair maternal behavior [ 175 ]; however, studies by Keverne and Kendrick [ 99 ] have reported that OXT’s effect on maternal neuroendocrine regulation is affected by the administration of opioid receptor blockers, limiting OXT release, a relevant issue when using analgesic treatment or other therapeutic protocols during parturition [ 27 ]. Moreover, nursing and maternal traits are highly motivated by parity, species, experience, and intrapartum events such as dystocia [ 87 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…The investigations of OXT in different anatomical regions and compounds are another research field. Recent studies in rabbits have shown that OXT antagonist administration does not impair maternal behavior [ 175 ]; however, studies by Keverne and Kendrick [ 99 ] have reported that OXT’s effect on maternal neuroendocrine regulation is affected by the administration of opioid receptor blockers, limiting OXT release, a relevant issue when using analgesic treatment or other therapeutic protocols during parturition [ 27 ]. Moreover, nursing and maternal traits are highly motivated by parity, species, experience, and intrapartum events such as dystocia [ 87 ].…”
Section: Future Directionsmentioning
confidence: 99%